2012
DOI: 10.1103/physrevstper.8.020113
|View full text |Cite
|
Sign up to set email alerts
|

Development and implications of technology in reform-based physics laboratories

Abstract: Technology has been widely involved in science research. Researchers are now applying it to science education in an attempt to bring students' science activities closer to authentic science activities. The present study synthesizes the research to discuss the development of technology-enhanced laboratories and how technology may contribute to fulfilling the instructional objectives of laboratories in physics. To be more specific, this paper discusses the engagement of technology to innovate physics laboratorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 34 publications
3
35
0
Order By: Relevance
“…Moreover, SBLs have some unique advantages that make them useful add-ons to physical laboratory activities (de Jong, Linn, & Zacharia, 2013;Rutten et al 2012). For example, scaffolding or guidance may be customized to individual needs (Chen et al, 2012;de Jong et al, 2013;Miao, Engler, Giemza, Weinbrenner, & Hoppe, 2012). Tenth graders using SBLs that guided them to identify problems, measure variables, and analyze and explain data outperformed their peers in traditional laboratories on both physics academic and science process skills tests (Yang & Heh, 2007).…”
Section: Simulation-based Laboratorymentioning
confidence: 99%
“…Moreover, SBLs have some unique advantages that make them useful add-ons to physical laboratory activities (de Jong, Linn, & Zacharia, 2013;Rutten et al 2012). For example, scaffolding or guidance may be customized to individual needs (Chen et al, 2012;de Jong et al, 2013;Miao, Engler, Giemza, Weinbrenner, & Hoppe, 2012). Tenth graders using SBLs that guided them to identify problems, measure variables, and analyze and explain data outperformed their peers in traditional laboratories on both physics academic and science process skills tests (Yang & Heh, 2007).…”
Section: Simulation-based Laboratorymentioning
confidence: 99%
“…For example, Internet technology may create an environment wherein collaborative, distant, interactive and inquiry-based activities are provided to foster knowledge construction and meaningful learning (Lee & Tsai, 2010). Recent review studies have indicated that learning environments can be enhanced by advanced computer technology such as simulations, probeware, augmented reality, and virtual reality applications, to facilitate learning and to shape instructional practices (Chen et al, 2012;Wang et al, 2014). Technology-supported learning environments (TSLEs) can help learners develop knowledge and skills that can be attained in conventional learning environments but in a more efficient way (Mayer, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…Their effects have been evinced in numerous studies by applying various technologies such as simulation [1][2][3][4], microcomputerbased laboratories [5][6][7][8], remote laboratories [9,10], and augmented reality [11,12]. The use of technology can support students' experience of inquiry and the constructive process of science in the laboratory [13]. Moreover, the technology could make inquiry less demanding for students by eliminating unrelated factors [13].…”
Section: Introductionmentioning
confidence: 99%
“…The use of technology can support students' experience of inquiry and the constructive process of science in the laboratory [13]. Moreover, the technology could make inquiry less demanding for students by eliminating unrelated factors [13]. In the laboratory activities, students may be discouraged when they fail to get the expected results after following procedures and not being able to figure out what was wrong [14] because many traditional instruments are unreliable.…”
Section: Introductionmentioning
confidence: 99%